Telemedicine in the Northern Territory: An assessment of patient perceptions in the preoperative anaesthetic clinic. (23rd January 2015) - Roberts, Simon; Spain, Brian; Hicks, Chelsea; London, James; Tay, Stanley
Abstract Objective We investigated patient perceptions of a virtual preoperative anaesthesia evaluation clinic linking Royal Darwin Hospital to Katherine Hospital. Design Descriptive study, cross‐sectional survey. Setting Regional and rural areas of Northern Territory, Australia. Participants Sample includes 27 respondents, five Indigenous, 18 non‐Indigenous and four unknown. Interventions Introduction of a preoperative anaesthesia evaluation clinic. Main outcome measures We designed a 10‐item, 5‐point Likert scale questionnaire assessing patient perceptions in four domains: (i) technical quality; (ii) perceived efficacy; (iii) affective patient experience; and (iv) patient preference. Qualitative responses are also reported. Results Twenty‐seven out of 35 patients (77%) completed the questionnaire. Ninety‐eight per cent were in positive agreement on technical quality with a mean score of 1.35 (SD: 0.53); Ninety‐five per cent on perceived efficacy, 1.35 (SD: 0.65); Eighty‐four per cent in negative agreement on affective patient experience (negative perception item), 4.19 (SD: 1.07); Eighty‐one per cent in negative agreement on patient preference (negative perception item), 4.23 (SD: 1.14). There were no significant differences in the answers between Indigenous (five patients) and non‐Indigenous patients (18 patients). Conclusion Our study confirms the acceptability of telemedicine in the remote assessment of preoperative patients in the Northern Territory, with positive perceptions in all four domains.